2009
DOI: 10.1021/jp906006w
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical and NMR Studies of Ring Puckering and cis/trans-Rotameric Interconversion in Prolines and Hydroxyprolines

Abstract: Nuclear magnetic resonance (NMR) and quantum mechanical (QM) studies have been carried out for proline (Pro) containing peptides: N-acetyl-l-proline (AcProOH) and N-acetyl-4-hydroxy-l-proline (AcHypOH). Preliminary results of variable temperature NMR measurements for Gly-Pro-Gly-Gly (GPGG), Val-Ala-Pro-Gly (VAPG), and Ala-Pro-Gly-Trp amide acetate salt (APGW) are also reported. The effect of solvent (D(2)O, DMSO-d(6) and CD(3)CN) on the pyrrolidine ring conformation and cis/trans-rotamerisation along the amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 47 publications
12
46
0
Order By: Relevance
“…The graphs are visualized using Chimera. 38 As an important and special feature of proline, the pyrrolidine ring puckering has been studied in detail, 4,[8][9][10][11][12][13][14][15][16][17] and proline's two preferred puckering states have been characterized very well. Usually, the pyrrolidine ring puckering is symbolized with two parameters-the pseudorotation phase angle and amplitude-that can be calculated either by the five ring-atom positions 18 or by the five endocyclic torsion angles χ j .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The graphs are visualized using Chimera. 38 As an important and special feature of proline, the pyrrolidine ring puckering has been studied in detail, 4,[8][9][10][11][12][13][14][15][16][17] and proline's two preferred puckering states have been characterized very well. Usually, the pyrrolidine ring puckering is symbolized with two parameters-the pseudorotation phase angle and amplitude-that can be calculated either by the five ring-atom positions 18 or by the five endocyclic torsion angles χ j .…”
Section: Introductionmentioning
confidence: 99%
“…24 As to the QM calculations, Kang and co-workers have thoroughly studied the preferable proline conformations using the different QM calculations, 11,12,14,16,25 and in a recent work Kang and Byun have compared the various QM calculations in studying the conformations of alanine dipeptide and proline dipeptide in the gas phase and in water. 26 Aliev and co-workers have studied the proline conformations using several QM calculations, 17 and they have also compared the results of NMR, DFT, and the empirical force field calculations. 15 Sahai et al have studied the four forms proline conformations, differing in N-and C-terminals, using the QM methods calculated at three levels of theory.…”
Section: Introductionmentioning
confidence: 99%
“…2). Since N-AcPro may exist in several conformations, as demonstrated by Aliev et al in their conformational NMR studies, 21,22 "-endo-" and -exo-" are used to differentiate between the C γ -endo and C γ -exo ring conformers, respectively, (see Fig. 2).…”
Section: Computationsmentioning
confidence: 99%
“…Employing the results of the above mentioned conformational NMR studies 21,22 we generated and optimized, at the B3LYP/6-1++G(d,p) level, six neutral structures of NAcPro (see Fig. 2).…”
Section: B Neutral Conformationsmentioning
confidence: 99%
“…Both PRO and HYP have the endocyclic ring structures that can pucker UP (positive χ 2 value, C γ exo conformation) or DOWN (negative χ 2 value, C γ endo conformation), which have been studied extensively. [3][4][5] It is found that PRO prefers the DOWN puckering at the Xaa position and HYP prefers the UP puckering at the Yaa position. 6,7 In the collagen model made of PRO-PRO-GLY triplets, prolines at the Xaa positions usually pucker DOWN and those at the Yaa positions usually pucker UP.…”
Section: Introductionmentioning
confidence: 99%